A Modified Bearing Capacity Model for Inclined Shallow Anchor Cable with Experimental Verification - Zhenhua Zhang; Guojuan Xu; Liangjun Dai; Tao Cheng; Banglu Xi; Mingliang Chen; Jiaqiang Yang (Applied Sciences)
Most theoretical models of shallow anchor cables do not take the effect of anchor inclination into consideration, which is an important factor influencing load distribution, stress concentration, and failure mechanisms. In this paper, a modified bearing capacity was developed for a single anchor cable, taking the anchor inclination into consideration, based on the principle of limit equilibrium. Then, a series of indoor pull-out tests of single anchors with different inclinations were performed, where the effects of the anchor inclination on the bearing capacity and failure mechanisms were carefully analyzed. The experimental bearing capacities were compared to the predicted data of the proposed modified model, as well as other existing experimental results, aiming to verify the applicability and accuracy. The results show that the bearing capacity increases with decreasing anchor inclination because the vertical component of the force acting on the anchor cable increases. The failure models of the anchor cables, pulled out at different angles, exhibit an asymmetric “inverted trumpet” shape, which is caused by the varying stress distributions around the anchor cable during pull-out. In addition, the bearing capacities of the theory differ very little from the experimental and previous results, with a max error of nearly 10%. This study confirms that the proposed model reliably captures the effects of anchor inclination, providing valuable insights for designing inclined anchors in engineering practice.